An increasing tendency of precocious puberty among Korean children from the perspective of COVID-19 pandemic effect - Choi, Kyu Hee; Park, Seung Chan (Frontiers in Pediatrics, 2022)
Introduction: This study was conducted to investigate changes and new trends over the past six years by analyzing the current status of precocious puberty (PP) treatment and treatment costs in Korea between 2016 and 2021. Materials and Methods: Annual and monthly number of patients diagnosed with PP from 2016 to 2021 were reviewed using the data from Healthcare Bigdata Hub. Annual medical insurance expenses for the treatment of PP were also reviewed. The data were compared by the gender of the patients. Results: The number of patients diagnosed with PP rose from 86,352 in 2016 to 166,645 in 2021, while medical expenses rose from \64,111,689 in 2016 to \134,642,100 in 2021. The percentage of male PP patients increased from 9.21% in 2016 to 19.55% in 2021. Conclusions: Increasing numbers of Korean patients diagnosed with PP. Consistent with the situation in other countries, the rapid increase in the number of cases since April 2020 appears to be a result of the COVID-19 pandemic. Also on the rise is the incidence of PP in males, which appears to be due to an increased awareness of the phenomenon. Further investigations are required to determine the possible causes in increasing prevalence of PP.